Impact of trust and knowledge in the food chain on motivation-behavior gap in green consumption. (May 2022) - Dong, Xuemei; Jiang, Baichen; Zeng, Hui; Kassoh, Fallah Samuel
Abstract: The motivations and barriers of the actual green purchase behavior are as real as the product itself, which makes it a systematic process to examine the inconsistency between consumers' motivations and their actual behavior (motivation-behavior gap). The study aimed to clarify the direct and indirect effects of motivations on the purchase behavior of green food. The proposed conceptual model was adopted from the Motivation-Opportunity-Ability (MOA) framework and was extended by adding the serial mediation of consumer perceived knowledge and trust as major constructs. Data were collected from 1788 consumers in China. Results provided support for the model and showed that perceived knowledge about the food supply chain could be both barrier and a positive factor of consumers' purchase behavior, which mainly depends on the trade-off between certification and planting knowledge. Differences in trust exist and consumers hold authorities and certification bodies more accountable than farmers and retailers. For the direct effects, food safety concern is positively associated with behavior, whereas environmental concern is not. Policymakers shall use the results to narrow the motivation-behavior gap, especially for emerging economies.